Sistem e-College Kolej Kediaman Kinabalu Universiti Malaya / Marcellia Godfrey - Marcellia, Godfrey (2003)
Computer Tecnology has been known as number one technology that being used all over the world. Finding information of one organization for examples, may takes a lot of time without this technology. In colleges, student information can be a very difficult job to do. To access and modify the student information will take luxury of time if it was done manually. e-College system using web based is a new application and still in the development process to improve its reliability and performance. There are a few problems in using an online system such as availability, accessing the devices, security access level, performance and reliability.Discussion on various aspects regarding e-College system especially using web based and online application will be presented as a method to access and modify the student information. In order to improve computer usefulness, I do take the challenge to improve by doing this project that include accessing and modifying data in student information. The goal of the project is to become the most leading online information solution in delivering web based to colleges, organization and consumers. It will provide each and every online student information with an engaging, effective and programmable surfing experiences that enhance knowledge, performance and proffesional value in the workplace.